2021
DOI: 10.1016/j.cmi.2021.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Prospective One Health genetic surveillance in Vietnam identifies distinct blaCTX-M-harbouring Escherichia coli in food-chain and human-derived samples

Abstract: Objectives: We performed a One Health surveillance in Hanoida region with a high-density human population and livestock production, and a recognized hotspot of animal-associated antimicrobial resistance (AMR)dto study the contribution of bla CTX-M -carrying Escherichia coli and plasmids from foodanimal sources in causing human community-acquired urinary tract infections (CA-UTIs). Methods: During 2014e2015, 9090 samples were collected from CA-UTI patients (urine, n ¼ 8564), pigs/ chickens from farms and slaugh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 29 publications
3
32
0
Order By: Relevance
“…The study also proved that the animal-associated CTX-M-producing E. coli strains or bla CTX-M carried plasmids were not direct sources of ESBL-EC infections in humans. 30 No TEM-, VEB-, OXA-, PSE-, SFO-types ESBL are detected in the study, which are relatively uncommon in Enterobacterales. No known ESBL encoding genes are identified in 10 ESBL positive isolates, suggesting that there may be new ESBL genes.…”
Section: Discussionmentioning
confidence: 71%
“…The study also proved that the animal-associated CTX-M-producing E. coli strains or bla CTX-M carried plasmids were not direct sources of ESBL-EC infections in humans. 30 No TEM-, VEB-, OXA-, PSE-, SFO-types ESBL are detected in the study, which are relatively uncommon in Enterobacterales. No known ESBL encoding genes are identified in 10 ESBL positive isolates, suggesting that there may be new ESBL genes.…”
Section: Discussionmentioning
confidence: 71%
“…In addition, Hoek et al suggested that ST155 and ST10 were most often found in broiler farms (Van Hoek et al, 2018). Not surprisingly, ST155 was the most common in several reports (Foster-Nyarko et al, 2021;Nguyen et al, 2021). In addition, seven ST156 strains were found only on farms, and they may be hosts for the transmission of the carbapenem resistance gene bla NDM , as previously reported (Tang et al, 2019).…”
Section: Similar Amr In Chickens and Farmsmentioning
confidence: 60%
“…Agriculture and Rural Affairs, P.R. China, 2019). According to previous reports, for each ton food animals are produced, 318 and 140 g antibiotics are consumed in 2013 (Zhang et al, 2015) and 2018 (Ministry of Agriculture and Rural Affairs, P.R.…”
Section: Similar Amr In Chickens and Farmsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the extent of transmission between these compartments remains uncertain, especially in high-income countries where hygiene standards probably limit the contaminations from non-human sources [9]. In particular, the role of the food chain is under debate [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%